Whole-rock chemical and Nd isotopic composition of a Late Proterozoic metasedimentary sequence in Ganderia: Kellys Mountain, Bras d’Or terrane, Nova Scotia, Canada - Barr, Sandra M.; Pin, Christian; McMullin, David; White, Chris E (Atlantic Geology, 2013)
The relationship between low-grade metasedimentary and high-grade paragneissic Precambrian rock units in the Bras d’Or terrane of central Cape Breton Island is a long-standing geological problem. Whole-rock geochemical and Nd isotopic data from representative components of these units in the Kellys Mountain area, the Glen Tosh formation and Kellys Mountain Gneiss, show strong similarity. Major and trace element characteristics suggest that protolith sediments for both units were wackes derived from felsic igneous sources and deposited at an active continental margin. Neodymium isotopic data in combination with previously published detrital zircon ages show that the sediments contained an ancient (ca. 2 Ga) end-member of recycled continental crust mixed with a juvenile component of Late Neoproterozoic age. The similarities suggest that the rocks represent the same sedimentary unit at different grades of metamorphism.